Membingkai Holistic Education dan Nilai-Nilai Institusi bagi Terwujudnya Revolusi Mental: Kajian Kontribusi Pemimpin Pendidikan melalui Pemberdayaan Nilai-Nilai Institusi - Munifah, Munifah (Didaktika Religia, 2015)
The paper highlights professional education management to empowerenvironmental and spiritual values as a source of learning and to improvecommunication and collaboration in o r der to enhance mental revolution. Asleaders of educational institutions, school principal is required to be more seriousin realizing the intensity, extensity, clarity value on maximum quality. Teachersas agents of a mental revolution sho u ld improve their competence especiallyin translating the curriculum in the learning activities so that they are varied,fun, democratic, and meaningful so as to build the personality and behavior ofstudents. Commitment and cooperation between the principal, the teachers, thecommunity, and the government in est a blishing noble values will accelerateIndonesia civilized nations as expected by the movement of a mental revolution.Key words: school principal, mental revolution, holistic education, values